Assessment of the Fire Hazard Category of Closed Spaces in the Oil Products Industry - Khojiev, Aliakbar A.; Yuldashev, Orunbay R. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the issues of assessing the fire and explosion safety of storage and processing facilities for petroleum products. The category of fire and explosion hazard and fire hazard of premises and buildings is determined for the most unfavorable period in relation to fire or explosion, based on the type of combustible substances and materials in the apparatus of the premises, their number of fire hazardous properties of the features of technological processes.